Pengaruh ph Dan Waktu Reaksi Pada Sintesis Hidroksiapatit Dari Tulang Sapi Dengan Metode Presipitasi - M Satria Haruda; Ahmad Fadli; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite is a mineral compound with chemical formula CA10 (PO4)6(OH)2 which can be used as implants in the human body. Hydroxyapatite can be synthesized from bovine bones using precipitation method. The aim of this study was to know the effect of pH and time of reaction to the characterization of hydroxyapatite made from using bovine bone. Bovine bones calcined at 1000 ℃ to produce calcium oxide (CaO). Then CaO is dissolved into distilled water and slowly mixed with phosphoric acid (H3PO4) and then set the pH 5, 7, 9, 11, and time of reaction 20, 40, 60, 80, 100, and 120 minutes. Then allowed to stand 24 hours and the precipitate is filtered. The results calcined sieve then characterized by XRD, FTIR and SEM. The effect of pH and time of reaction in the synthesis of hydroxyapatite seen in the XRD analysis showed the higher peaks than the other at the same peaks and the FTIR analysis looks at the increasingly sharp steepness wavelength at PO43- functional groups and OH- when the pH is higher. Based on the results , the hydroxyapatite at pH 11 has a purity of 99.7 % and crystanility of 98.33 % , while the pH 5 has a purity of 97.5 % and crystanility of96.00 %. Time of reaction at 100 minutes showed a purity of 99.8 % and crystanility of 92.82 % and purity of 92.9 % and crystanility of 84.99 % for 20 minutes. .Keywords: hydroxyapatite, pH, precipitation, time of reaction